Evaluation of macro-invertebrates as bio-indicators of water quality and the assessment of the impact of the Klein Plaas dam on the Eerste River - Bredenhand, Emile (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Conservation Ecology and Entomology)--University of Stellenbosch, 2005.